2020
DOI: 10.22630/esare.2019.3.19
|View full text |Cite
|
Sign up to set email alerts
|

Overinvestment in Polish Agriculture

Abstract: The purpose of this paper was to assess the level of overinvestment in Polish farms grouped by economic size. As the volume of investments clearly continues to grow, the authors noticed the need to address that problem. Using FADN data, they developed their own method for measuring overinvestment, and identified its size and extent. Indeed, overinvestment proves to be widespread in Polish agriculture. The reasons probably include inadequate subsidies allocated under European Union aid schemes, and improper far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, this topic still involves considerable discrepancies [50,51], which enables the division of the study areas into regions, some of which may be struggling with agricultural inefficiency. One type of inefficiency is investment inefficiency, which is closely associated with overinvestment, defined as a situation in which the capital-labour ratio increases while labour productivity decreases [52]. Overinvestment in the economy is most simply defined as a situation in which economic units invest more than they should [53].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this topic still involves considerable discrepancies [50,51], which enables the division of the study areas into regions, some of which may be struggling with agricultural inefficiency. One type of inefficiency is investment inefficiency, which is closely associated with overinvestment, defined as a situation in which the capital-labour ratio increases while labour productivity decreases [52]. Overinvestment in the economy is most simply defined as a situation in which economic units invest more than they should [53].…”
Section: Literature Reviewmentioning
confidence: 99%
“…not to lead to an overinvestment. [ 31 ] showed that overinvestment, which does occur in Polish agriculture, affects economically weaker farms to a greater extent, thus access criteria for EU funds might mitigate this effect.…”
Section: Discussionmentioning
confidence: 99%
“…This process can also be noticed in the agricultural sector and affects specific groups of farms to various degrees. This results in the emergence of what is referred to as overinvestment, i.e., a condition where long-term investments are excessively high compared to the production potential (mainly land resources) and, ultimately, become economically unviable [46]. Optimum investment means a situation where the assets-to-labor ratio (ALR) of a farm grows at the same pace as labor productivity (LP) [47].…”
Section: Introductionmentioning
confidence: 99%
“…Optimum investment means a situation where the assets-to-labor ratio (ALR) of a farm grows at the same pace as labor productivity (LP) [47]. In turn, overinvestment takes place when the assets-to-labor ratio grows while labor productivity declines or remains constant [46]. The inefficiency of investments brings many negative effects to farms.…”
Section: Introductionmentioning
confidence: 99%